Migration of Scaphoideus titanus Ball from the surrounding vineyards into the nursery - Primož GRIŽON; Gabrijel SELJAK; Irma VUK (Acta Agriculturae Slovenica)
A one-year study of the mobility of leafhopper Scaphoideus titanus Ball (ST), vector of Flavescence dorée phytoplasma, was conducted in 2009 and included three Slovenian nurseries in the Primorska winegrowing region, as well as two Italian and one Swiss nursery, and was aiming at evaluating the risk of spreading ST with vine propagating material. The presence of ST was monitored by the means of yellow sticky traps that were placed at three distances in the nurseries and the nearby vineyards on three parallel lines (replicates). The traps were equidistantly placed from the nurseries’ and vineyards’ borders in order to determine the possible distance gradient. The monitoring started in the latest nymphal stages (middle of June) and terminated in the first decade of October. Insecticide treatments with deltamethrin (Decis 2.5 EC) were applied in nurseries, according to the instructions for use and recommendations for suppression of ST. On all Slovenian plots in the vineyards, the population level of ST was high (1796 adults in average / vineyard or 18 adults per trap / week), which indicated a great migration potential of the vector towards the nurseries. Catches were very low (54 adults in average / nursery or 0.4 adults / trap / week) on two nurseries’ plots (Lože and Slap), although high numbers of ST adults were caught in the adjacent untreated vineyards. On the Poreče nursery plot, insecticide treatments were not sufficient to avoid high numbers of ST catches (in total 481 adults or 3 adults / trap / week). This could be related to the sub-optimal timing of the first insecticide treatment and/or migration of adults from two nearby untreated vineyards located at a distance of 70 and 150 m. The distance between the nurseries and vineyards did not affect ST catches in the nurseries.